Pendampingan Optimalisasi Peran Sumberdaya Manusia Perusahaan Kontraktor di Banjarmasin dan Palangkaraya untuk Peningkatan Kinerja Organisasi: Assistance in Optimizing the Role of Human Resources of Contractor Companies in Banjarmasin and Palangkaraya to Improve Organizational Performance - Suyoto, Yohanes Totok; Haludin, Guntur; Prasetio, Teguh (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
More than in the previous era, after the COVID-19 pandemic, companies must build effective human resource management (HRM) to improve employee performance and work culture. This condition requires an organizational form and HRM system relevant to performance needs and demands. PT Gagah Putera Satria needs to transform employees' systems, processes, and work culture to increase their performance as a company engaged in the service sector. Improving and enhancing the performance of the human resource organization is the key to the company's success in achieving the expected performance. That is why the company developed a comprehensive HRM as a major project along with the change in the form of the company, which was initially a heavy equipment rental company, shifted to heavy equipment contractors in the mining industry in Kalimantan. This assistance aims to help the company improve HRM performance. The activities include mapping the actual conditions of the problems experienced related to the company's HRM, restructuring the human resource organization, and disseminating recommendations for HRM performance improvement programs to principals and employees of the head office and project office at the site. The results of the assistance are the formation of an integrated structure of the HRM system, the operation of the human resource management process with a streamlined structure and a more effective process, and the increased managerial skills of the HRM personnel of the company.